PENGARUH TES FORMATIF TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 1 KUANTAN SINGINGI BATU AMPAR BERINGIN TELUK - Arofah Julanda; Zulhaini Zulhaini; Helbi Akbar (Universitas Islam Kuantan Singingi, 2020)
In the world of education is inseparable from the test/evaluation and result to see the exent of student development in the learning process, especially moral study. In the research observation in MAN 1 Teluk Kuantan, Batu Ampar Beringin Teluk found several symptoms related to the effects of formative test on student learning outcomens. Namely: 1) formative tests have been conducted but there are still students who have no experienced an increase in learning. 2) students have complained abaut formative tests. 3) when oral tests are conducted only a portion of students answer. 4) students do not understand formative tests. 5) students learning outcomes are low. This research has several puposes for the writher and another students, such as to know how big the effect of using formative test on student’s rearning result especially in MAN 1 Kuansing Batu Ampar Beringin Teluk. This research was conducted in Quantitative with the saccumululation at observation , interview, questionnaire and documentation and was analyzed by using simple linier regression. Based on the result of the effect using formative test on student learning result in MAN 1 Kuansing Batu Ampar Beringin Teluk, proved by the effect of formative test (variable X) toward student’s learning result (variable Y) there was an effect about 0,003 %. From the result, it can be answered the effect of X factor on Y. Besaide that, there was other factors effecting the case such as Attitude, teacher, facilitate, education and education value. Kata Kunci: Tes Formatif dan Hasil Belajar